RODEO: An algorithm and Google Earth Engine application for river discharge retrieval from Landsat. (February 2022) - Riggs, Ryan M.; Allen, George H.; David, Cédric H.; Lin, Peirong; Pan, Ming; Yang, Xiao; Gleason, Colin
Abstract: Satellite remote sensing of river discharge (RSQ) algorithms provide a useful source of observations to supplement river gauge records. RSQ algorithms have existed for over a decade yet their widespread use has been impeded by a lack of operational usability and quantitative characterization of uncertainty. Here we present RODEO, an algorithm for estimating river discharge using Landsat observations in near-real time. RODEO is validated with 456 gauges (median Kling-Gupta efficiency = 0.3) and uses a novel quantile rating curve technique that pairs Landsat river widths with discharge estimates from a global hydrologic model. RODEO also characterizes the uncertainty of RSQ estimates (estimated root-mean-square error = +7%), enabling RSQ retrievals to be used for data assimilation into hydrologic models. With the goal of expanding the RSQ user base, the RODEO algorithm is implemented as a freely available, off-the-shelf cloud-based Google Earth Engine application that provides RSQ estimates across North America from 1984-present. Highlights: We present RODEO, a user-friendly application for estimating river discharge from Landsat 5, 7, and 8. River widths can be quickly extracted from Landsat images and used to estimate discharge. RODEO characterizes discharge uncertainty allowing for remote sensing measurements to be used for data assimilation.